Social Media as a Site of The Qur’anic Reception A Case Study of the Podcast Login Episode “Dicky Difie "Apapun demi Nyokap, Jadi M1skin Gua Siap!!!”: Media Sosial sebagai Sarana Resepsi Al-Qur'an: Studi Kasus Podcast Login Episode “Dicky Difie "Apapun demi Nyokap, Jadi M1skin Gua Siap!!!” - Suhada, Farhan; Juansa Putra , Deden; Rifki Naswa, Ikhsan (Takwil: Journal of Quran and Hadith Studies, 2025)
This article examines the reception of the Qur'an on social media through an analysis of a podcast episode titled ‘Dicky Difie: Anything for my mum, so I'm willing to be m1skin!!’. The primary focus is on Qur’anic values, particularly those related to filial piety, sacrifice, and ethical commitment, which are reinterpreted and recontextualised within social media narratives. This study aims to explore the reception of the Qur'an on social media: a case study of the podcast Login episode: “Dicky Difie: anything for nyokap, so m1skin I'm willing!!!”. Using Ahmad Rafiq's living qur'an theory approach which emphasizes the reader's response to the Qur'an. The reception initiated by Ahmad Rafiq consists of three forms and two of them can be found in this Login podcast, namely exegesis reception in the form of understanding the Qur'an in accordance with existing translations or interpretations, aesthetic reception, namely interpreting the Qur'an based on its beauty either musically or in the form of calligraphy art. Using the content-analysis method, which analyzes the form of reception displayed in the content, then criticizes the transformation in it. This article concludes that QS. Luqman: 12-14 in this podcast has different interpretations from the scholars of tafsir who interpret this verse as a form of honouring the role of parents, especially mothers who have sacrificed for their children, whereas in this podcast, the understanding of QS. Luqman: 12-14 is interpreted as a child's negligence in giving attention to the role of the mother, who serves as the gateway to guidance for a child. Additionally, reciting the Qur'an with proper pronunciation (tartil) is highly appreciated as a testament to the miraculous nature of the Qur'an, which possesses a high artistic value within it.